Approach to echocardiography in ARDS patients in the prone position: A systematic review. Issue 2 (18th January 2022) - Ajam, Mustafa; Drake, Matthew; Ran, Ran; Mukundan, Srini; Masri, Ahmad; Rahmouni, Hind
Abstract: Echocardiography is commonly utilized in patients with acute respiratory distress syndrome (ARDS) for assessment of cardiac function, volume status, and the potential development of acute cor pulmonale. In severe ARDS, prone positioning is frequently used, which imposes technical challenges during transthoracic echocardiography (TTE) image acquisition. Moreover, prone positioning can affect cardiopulmonary function in ways that are reflected on the echocardiographic findings in this position. Historically, a transesophageal approach was recommended when a patient is prone, with few studies reporting utility of TTE in this setting. However, recent publications have begun to address this knowledge gap. This review explores recent literature addressing the use of TTE in prone patients with ARDS, with a special focus on the cardiopulmonary effects of proning and potential solutions to the technical difficulties that arise in this position.